Community Based Assessment of Behavior and Awareness of Risk Factors of Cystic Echinococcosis in Major Cities of Pakistan: A One Health Perspective - Khan, Aisha; Ahmed, Haroon; Amjad, Shaheera; Afzal, Muhammad Sohail; Haider, Waseem; Simsek, Sami; Khawaja, Mudassar Rashid; Khan, Danish Hassan; Naz, Shumaila; Durrance-Bagale, Anna; Shabbir, Rana Muhammad Kamran; Arfeen, Raja Zoq Ul; et al. (Frontiers in Public Health, 2021)
Background: The parasitic disease, cystic echinococcosis (CE), is a serious health problem in Pakistan. Risk of disease transmission is increased by economic and political instability, poor living conditions, and limited awareness of hygienic practices. The current study aimed to investigate the community perception and awareness regarding the risk factors of CE in Pakistan, from a One Health perspective. Methods: We conducted a community-based survey involving 454 participants in the major cities of Pakistan. Quantitative data based on knowledge, attitude, and practices (KAP), the One Health concept, risk factors, and community perception of CE among the general population of major cities of Pakistan were collected. The questions included those related to knowledge, attitude, practices, One Health concept, risk factors, and community perception. Chi-square test was applied to find out the associations regarding KAPs across socio-demographic parameters. Results: Knowledge, Attitude and practices had no significant associations with sociodemographic aspects such as age, sex, religion, ethnicity, education, marital status, occupation, or financial status of the participants. The findings indicated a lack of awareness about CE among the participants. Respondents were unaware of the risk factors and the One Health concept of CE. However, the community attitude and perception were positive toward the control of CE. Conclusions: Illiteracy, deficient sanitation systems and lack of awareness are the contributing factors of CE in Pakistan. It is necessary to aware the ccommunity regarding CE and its importance. Increasing this awareness represents an important step toward the eradication and control of CE.